The Properties of Thermal Waves Affecting Iraq (Journal of the College of Education for Women, 2019)
This research aims at studying each of the cold and hot thermal wavelengths affectingIraq for a minimum climatic course of 11 years beginning from 1992 till 2002. Three stationswere selected including the parts of Iraq surface: Mosul, Baghdad and Basrah.The wave days were also connected with the related climatic elements represented bythe wind direction and speeds and the relative humidity. It was shown that Iraq is affected bythe rates of hot thermal wave lengths greatly compared to the rates of cold wavelengths. Theresults suggested that the highest rate of hot and cold wavelengths recorded over Basra stationwas (3.5) days for the cold and (5) days for the hot. While the lowest rates was at Mosulstation amounting (2.4) days for the cold and (4.5) days for the hot. The research showed thatthe highest total rate of the days number of cold wavelengths was for the deepest wave, whilethe shallow wave recorded the highest rate of days number of hot wavelengths for the threestations. It was noted, in the last years of the study period, a decrease in the rates of coldwavelengths and an increase in the rates of hot wavelengths due to the global warming. Theresults showed that the speeds of the winds accompanying the rate of thermal wavelengthswere between static and light for cold waves and light and moderate for hot waves.